Implementation Of CPTED (Crime Prevention Through Environmental Design) By Aviation Security Sultan Syarif Kasim II International Airport Pekanbaru In The Prevention Of Narcotics Smuggling - Ramadan, Heri; Riky Novarizal (Sisi Lain Realita, 2026)
Narcotic smuggling at airports represents a serious threat to aviation security and operations. This study examines the implementation of CPTED (Crime Prevention Through Environmental Design) by Aviation Security (AVSEC) at Sultan Syarif Kasim II International Airport, Pekanbaru, in preventing narcotic smuggling. Utilizing a descriptive qualitative method, data was collected through observation, documentation, and interviews with the Chief Aviation Security, Supervisor Aviation Security, Senior Aviation Security, Junior Aviation Security, and Basic Aviation Security. The research findings indicate a fluctuating trend (increase and decrease) in the number of drug smuggling cases from 2020 to 2022, followed by a resurgence in the number of cases between 2023 and 2026. The implementation of CPTED is evidenced by the comprehensive use of CCTV surveillance cameras, access restrictions, routine personnel patrols, and strict inspections of passengers carry on items and baggage using x-ray for in airport areas such as Domestic PSCP, International PSCP, reconciliation room area, ASCP 1 area and cargo warehouse area. Furthermore, it includes facility maintenance and the routine activities of airport staff or events held at the airport terminal that support the creation of a positive image within the airport premises.